TANJUNG (Mimusops elengi L.) AND KIARA PAYUNG (Filicium decipiens (Wight & Arn).) Thwaites) ROOT DISTRIBUTION ANALYSIS IN TWO DIFFERENT PLANT MEDIA - Faiha Namada, Sheila
Infrastructure construction such as tunnel at Cisumdawu Freeway caused land without vegetation with bad condition of physics, chemical, and biology. The existence of vegetation can fix the soil in its surface movement and it is also can fix unstable soil. The purpose of this research is to estimate root distribution in two different media represented by root shallowness index and define the effect of organic compound towards root shallowness index. This research located in Screenhouse Kampus ITB Jatinangor for 3 months. Plant species that is used in this research are tanjung (Mimusops elengi) and kiara payung (Filicium decipiens), using 60 samples of each species. Used plant media is the soil from empty land above the tunnel. Measured parameters are diameter and proximal roots direction (first root branching from the stem base), root length, and stem diameter. Treatments are applied to each species, control (without organic compound) and 50% organic compound addition. Analysis of variance between plant species and organic compound addition is done to find out how much the treatments affect root shallowness index. The result of this research shows that the average of root shallowness index from controlled tanjung and index from tanjung with 50% organic compound addition in a row are 0,037 and 0,055. The average of root shallowness index from controlled kiara payung and index from kiara payung with 50% organic compound addition in a row are 0,033 and 0,05. 50% organic compound addition affects the increasing value of tanjung and kiara payung root shallowness index. Tanjung root shallowness index increasing 3,5% and for kiara payung is 3,4%. That increment could indicate that more organic compound should be added to increase root shallowness index, with high index it is also could stabilize the soil surface.